Comparison of two maximal anaerobic cycling tests - Tossavainen, M.; Nummela, A.; Paavolainen, L.; Mero, A.; Rusko, H. (International Journal of Sports Medicine, 1996)
The purpose of this study was to compare two cycle ergometer modifications of the maximal anaerobic running test (MART) with each other and with the MART. Ten male physical education students performed the two maximal anaerobic cycling tests (MACT) in a random order and the MART between the MACTs. Each test consisted of n.20-s exercise bouts with a 100-s recovery period between them. Based on the ACSM equations the oxygen demand of the initial bout in each test equalled 56 ml.kg-1.min-1 and the increase for each consecutive bout was 6 ml.kg-1.min-1. In MACTres the resistance was increased and the pedalling frequency was kept constant (100 rpm) while in MACTfreq the frequency was increased and the resistance was constant (0.077 x body weight). In the MART the velocity of the treadmill was increased and the slope was constant (4 degrees). Blood lactate (BLa) concentration was measured at rest, 40 s after each run and during a 10-min recovery period. Maximal power (Pmax) was similar in the MART, MACTres and MACTfreq (107 +/- 4, 107 +/- 8 and 105 +/- 6 ml.kg-1.min-1, respectively) while significant differences (p < 0.05) were observed in the peak BLa (12.8 +/- 1.3, 15.6 +/- 1.7, and 14.7 +/- 2.1 mM, respectively). BLa was lower in the MACTfreq than in the MACTres until the oxygen demand of 86 ml.kg-1.min-1 and it was higher in both MACTs compared to the MART at each workload. We concluded that the MART can be modified for the bicycle ergometer although metabolic acidosis was greater in bicycle modifications. Further, the comparison of the MACTres and MACTfreq showed that blood lactate accumulation was greater at the higher pedalling frequency.